DEVELOPMENT STRATEGY FOR HISTORICAL RELIGIOUS TOURISM VILLAGES: A CASE STUDY OF RANTAU PANJANG VILLAGE - Sinar, Tengku Mira Rozanna; Harahap, R. Hamdani; Humaizi, Humaizi; Subhilhar, Subhilhar (International Conference On Social Science Education, 2024)
Rantau Panjang Village is one of the villages in Deli Serdang Regency that has the potential for sustainable historical religious tourism with several historical buildings such as the Basyaruddin Grand Mosque and the Green Dragon Temple. The purpose of this research is to analyze the development strategy of a historical religious tourism village in Rantau Panjang Village, Deli Serdang Regency, North Sumatra Province, Indonesia. The research method is descriptive and qualitative using SWOT analysis to analyze the uncertainty of internal environmental factors and the external environment. SWOT analysis is the right alternative to determine the strategy of Rantau Panjang Village to develop its potential to become a sustainable historical religious tourism village. Where SWOT analysis can analyze strengths, and Weaknesses which are part of the internal factors of Rantau Panjang Village and Opportunities, Threats which are part of external factors. The results of the study found strategic steps that must be taken by Rantau Panjang Village in order to become a sustainable historical religious tourism village supported by high commitment and development of facilities and infrastructure and paying attention to environmental damage around Rantau Panjang Village.